Improving the sporulation of Eimeria tenella oocysts purified from chicken faeces - Nurfazila Latif,; Aravind Marcus,; Bura Thlama Paul,; Suhaili Mustafa,; Muhamad Hakim Mohd Ali Hanafiah,; Lirong Yu Abit,; Sharifah Salmah Syed Hussain,; Nor Azlina Abdul Aziz,; Loo, Shu-San; Wan, Kiew Lian; Altwaim, Sarah A.; Juriah Kamaludeen, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Coccidiosis is a major and recurrent intestinal disease in the chicken industry caused mainly by Eimeria tenella and it is the best-known and most economically significant species in poultry. Oocyst purification is a common and critically important method used for the study of Eimeria species. Various methods have been used for the purification of coccidia oocysts. However, no study has outlined the most effective method for increasing the sporulation of Eimeria tenella oocysts. Thus, the study compared and validated the applications of the three common oocyst sporulation methods, viz: (i) forced aeration without a shaker, (ii) forced aeration in combination with a shaker, and (iii) magneto base without forced aeration. A total of 9 individual 21-day-old broiler chickens were inoculated individually with a single 1 mL dose containing 2000 Eimeria tenella oocysts via oral gavage. Water and food were provided ad libitum throughout the experimental period. Pooled group faecal samples were collected on the 7 day post-infection. The average (range) number of sporulated oocysts counts for the forced aeration without shaking was 2250 (1000-2000), forced aeration in combination with shaking was 2000 (1000-1500), and the magneto base without forced aeration was 5500 (2000-3500). The results from the study indicated that the magneto base without forced aeration was the most effective method for enhancing the sporulation of Eimeria tenella oocysts.